CAVE-2 (Cetuximab-AVElumab) mCRC: A Phase II Randomized Clinical Study of the Combination of Avelumab Plus Cetuximab as a Rechallenge Strategy in Pre-Treated RAS/BRAF Wild-Type mCRC Patients - Napolitano, Stefania; Martini, Giulia; Ciardiello, Davide; Di Maio, Massimo; Normanno, Nicola; Avallone, Antonio; Martinelli, Erika; Maiello, Evaristo; Troiani, Teresa; Ciardiello, Fortunato (Frontiers in Oncology, 2022)
Introduction Immunotherapy has limited efficacy in metastatic colorectal cancer (mCRC). Understanding mechanisms mediating immune resistance in microsatellite stable (MSS) colorectal tumors remains an ongoing challenge. Novel combination immunotherapy-based approaches have been developed under the rationale of overcoming immune resistance and developing effective immune response against colorectal tumor cells. Preclinical studies have demonstrated that cetuximab may modulate immune response to cancer cells. In this scenario, the inhibition of PD-L1 with IgG1 MAb avelumab in combination with anti-EGFR IgG1 monoclonal antibody cetuximab could be a strategy for potentiating antitumor activity. The CAVE phase II single-arm clinical trial provided the first evidence of clinical activity of combining cetuximab plus avelumab in 77 patients with RAS wild-type (WT) mCRC. This combination had a good toxicity profile, with a low rate of common grade 3 adverse events. Patients and Methods Based on results obtained with the CAVE clinical trial, here we describe the design and rationale for the phase II, randomized CAVE 2 clinical study of the combination of avelumab plus cetuximab as a rechallenge strategy in pre-treated RAS, BRAF WT mCRC patients treated in first line with chemotherapy in combination with cetuximab and who have had a clinical benefit (complete or partial response) from treatment. A total of 173 patients will be randomized (2:1) to cetuximab + avelumab (115) or cetuximab as a single agent (58). The primary endpoint is overall survival. Key secondary endpoints include overall response rate, progression-free survival, and safety. For each patient, before treatment, a blood sample will be obtained and analyzed for circulating free tumor DNA according to NGS (Foundation/Roche), to identify RAS/BRAF WT patients to be enrolled. The same procedure will be performed at the progression of the disease. Additional blood/plasma, tumor, and fecal samples will be collected and centrally stored for additional translational studies. Discussion This study will provide the rationale to test immunotherapy-based combinations in the clinical setting, offering new opportunities for RAS WT mCRC patients. Clinical Trial Registration [https://clinicaltrials.gov/ct2/show/NCT05291156], identifier [NCT05291156].